TEACHING ENGLISH TO YOUNG LEARNERS: BELIEFS AND PRACTICES:A Case Study of the English Teachers of the Public Elementary Schools in Bandung Kulon Sub-District - Nurlaelawati, Iyen (2009)
This thesis reports the portrait of teaching English in elementary schools in Bandung. This study tried to address three main issues: (1) the teachers' beliefs about children's characteristics, (2) the teachers' beliefs about children's ways of learning, and (3) their implications in teaching English to young learners in public elementary schools. Three teachers of two public schools in Bandung Kulon, West Java, Indonesia, participated in this study. The teachers were given a set of questionnaire in order to gain the data about their beliefs. They were also observed while teaching to their students to seek information on the teaching practices they usually administered. To validate the data they were interviewed. The study discovered that the participants had certain beliefs about children. The participants believed that children were active in playing and being curiosity. The children were believed to have great imagination and capacity in using their limited resources of language. The participants also had certain beliefs in terms of the children's ways of learning. They thought children were active learners. Children learned from their surrounding, and more knowledgeable persons, like adults and their peers. Children were also believed to have their own unique intelligences-the participants called it talent, one child might have different intelligence from the others. Regarding the participants' teaching practices, the findings showed that in general they taught their students using the methods that sometimes did not match children's characteristics. Their focuses of teaching were doing what were instructed in the textbook and explaining grammar. Children were not given enough space to deal with their English. The teachers still became the ones who had the control over the activities in their classrooms. Thus, it is recommended that the teachers and school authorities be aware of the needs of the teachers to improve their professionalism-English and teaching competencies. It is also suggested to do further study to help teachers develop their expertise.